A study of Lumban embroidery - Taneza, Rhea Carmela M.
Philippine hand embroidery has been recognized as one of the most beautiful needlework in the world. This is attested by the numerous collections of old pieces of Philippine embroidered items in museums all over the world (Montinola, 1991). In times of mass commercialization, however, less and less importance is given to the preservation of quality of hand embroidery and more on the mass production of garments. Even in rural areas where embroidery thrives as a cottage industry, the effects of consumerism have slowly permeated. Due to change in market demands and consumer needs, changes in the mode of embroidery, the designs and techniques used appeared resulting in the depreciation of the traditional hand-woven embroidery. This study was conducted to describe embroidery designs and techniques in one of the rural areas where hand embroidery still exists: Lumban, Laguna. Specifically, it sought to describe the embroidery in the said area in terms of the following aspects: mode of embroidery, process, materials and tools, motifs, colors and application to apparel. Data was gathered through guided interview with selected people in Lumban who are directly and indirectly involved with the workflow of the embroidery activity. Observations were also made on the embroiderers in actual work to see firsthand the process of embroidery. Key informants such as the Lumban residents and municipal officers were also interviewed. Supplementary data were gathered from books and articles regarding embroidery. This study finds worth in its contribution to the growth of embroidery as an embellishment that makes Filipino embroidered garments one of the expertises of Filipinos and what they are known for internationally. Developments in embroidery in Lumban Laguna are: the introduction of the machine mode of embroidery, the specialization of skills for each aspect of the embroidery process, the use of electric embroidery machine for piercing the outline of design for stamping, the change from the old style of fully-embroidering to the current style of scattered and lesser embroidery, the introduction of painted designs, painted and dyed fabrics and beading, and the addition of items to be embroidered such as covers for appliance and furniture and cell phone cases. Changes in the different aspects mentioned were mostly influenced by the market demands, changes in consumer needs and wants and the introduction of new technologies.